Chlamydomonas reinhardtii-expressed multimer of Bacteriocin LS2 potently inhibits the growth of bacteria. (August 2020) - Liu, Yan-Xia; Li, Zhen-Fang; Lv, Yu-Jie; Dong, Bin; Fan, Zhen-Chuan
Graphical abstract: Highlights: 3×Bacteriocinis expressed in Chlamydomonas reinhardtii for the first time. C. reinhardtii -derived 3×Bacteriocin LS2 inhibits bacteria of both Gram-positive and Gram-negative. C. reinhardtii -derived 3×Bacteriocin LS2 is thermostable and insensitive to pHs and proteases. C. reinhardtii -derived 3×Bacteriocin LS2 is nontoxic to mammalian cells; C. reinhardtii -derived 3×Bacteriocin LS2 inhibits bacteria by disrupting their membranes. Abstract: Bacteriocin LS2 was isolated from the Lactobacillus salivarius BGHO1 strain in 2012. Since then, its antibacterial activity has not been examined. Here, Chlamydomonas reinhardtii was used to express a C-terminal hemagglutinin (HA) and 6×His double tagged three repeats of Bacteriocin LS2 (3×Bacteriocin LS2). 3×Bacteriocin LS2 expression was stable following passaging in C. reinhardtii cells for six months and its yield accounted for 0.28% of total soluble proteins of the host cells. C. reinhardtii -derived 3×Bacteriocin LS2 inhibited the growth of four tested bacteria of both gram-positive and gram-negative with minimum inhibitory concentration (MIC) values between 75 and 90 μg/mL, indicating that this peptide is more potent than other bacteriocins like nesin and bacteriocin MA047A which have a MIC beyond 165 μg/mL in general. The recombinant 3×Bacteriocin LS2 maintained high stability over a wide range of temperature and pHs, showed tolerance to proteases, exhibited low hemolytic activity against rabbit erythrocytes and low cytotoxicity to human embryonic kidney 293 T (HEK 293 T) cells. In addition, C. reinhardtii -derived 3×Bacteriocin LS2 penetrated cell membranes and destroyed the morphology of targeted bacterial cells to different extents. In summary, our study shows that C. reinhardtii can be used as a platform for the production of active Bacteriocin LS2.